STREET-LEVEL ACTOR DYNAMICS IN THE IMPLEMENTATION OF CHARACTER EDUCATION POLICY: THE GAPURA PANCA WALUYA PROGRAM - Lukman Hakim; Muradi; Neneng Yani Yuningsih (SOSIOEDUKASI, 2026)
Character education constitutes a strategic public policy instrument for strengthening citizenship quality and social resilience. In Indonesia’s decentralized governance system, character education policy is translated into various regional initiatives, including the Gapura Panca Waluya Program in West Java Province. Although normatively formulated by the provincial government, the program’s implementation at the school level demonstrates varying outcomes and practices that do not always reflect its transformative objectives. This study aims to analyze the dynamics of street-level actors in the implementation of the Gapura Panca Waluya Program and to identify structural challenges and patterns of implementation across schools. The research employs a qualitative policy study design based entirely on secondary data. Data were collected from regional policy documents, official government reports, educational evaluation records, and relevant academic literature. Document analysis was conducted to examine policy narratives, actor roles, and the relationship between policy design and school-level practices. The findings reveal that principals and teachers play a central role in interpreting and operationalizing character education policy. However, broad discretionary space, uneven institutional capacity, and evaluation mechanisms emphasizing administrative compliance encourage ceremonial and symbolic implementation patterns. Variations across schools reflect the interaction between local discretion and regional policy design. The study concludes that effective character education policy depends not only on normative clarity but also on coherent policy design, substantive supervision, and sustained capacity strengthening at the school level.